Investigation of Bending, Sound Absorption, and Damping Properties of AZ91D-Swivel Plate. (22nd May 2020) - Annamalai, Saravanan; Periyakgoundar, Suresh; Paramasivam, Kumaravel; Selvaraj, Aravindha Balaji
Abstract : A comparison was made between Mg alloy and A3 steel on weight, bending, sound absorption, and vibration conditions. In this study, a swivel plate, which is used in rotating car seats, is to be taken into consideration for finding bending, natural frequency, and frequency under static loading conditions. The swivel plate is generally made up of A3 steel plate; instead, we have replaced that with Mg alloy (AZ91D) plate. Stiffness, flexural strength, natural frequency, frequency under different static loading conditions, and sound absorption capacity were obtained through experimental methods. Finally, it was concluded that the damping capacity of Mg alloy of swivel plate is higher, has better stiffness, and incurred weight reduction by 26.58% less than that of the A3 steel. Also, the Mg alloy material exhibits better specific flexural strength, and specific flexural modulus and sound absorption coefficient are 11.76% and 25% higher than those of A3 steel at higher frequency level (2000 Hz) and at lower frequency level (100 Hz).